Effect of sonochemical impact on the duration of fresh juices storage - V. A. Demchenko; J. F. Zikrullaev; I. V. Asfondyarova; V. V. Nazarova (Новые технологии, 2019)
At present in Russia there is a tendency of increased consumption of natural fruit and vegetable juices by the population. A large proportion falls on 100% fresh juice. Among all the juices consumed in our country, orange juice is the most popular one. Substances found in citrus fruits have anticarcinogenic, antiviral and antioxidant effects. But from the time of production to the time of juice consumption, a number of complex chemical changes occur, which spoil the product. Due to the short shelf life of fresh juices, as well as decrease in quality indicators during their storage, studies have been carried out on the effect of ultrasonic processing on the quality of fresh orange juice, which are relevant and solve the problem of supplying food market with quality food. The purpose of this study is to increase the shelf life and preserve the quality indicators of fresh orange juice. When using organoleptic and microbiological research methods conducted during the experiment, the following results have been obtained: it’s been found that the use of ultrasonic treatment significantly improves the quality of juice during storage. In particular, it’s been recorded: the absence of sediment formation during storage of fresh orange juice samples treated with ultrasound; preservation of bright color inherent in this product; ultrasonic treatment has significantly reduced the development of the total bacterial contamination of the resulting product. An optimal operation mode of the equipment has been proposed - the recommended treatment intensity is 75 W for 3 minutes, until the temperature in the product reaches 60°C.